Evaluation of inherent factors on flowability, cohesiveness and strength of cementitious mortar in presence of zeolite powder. (30th July 2019) - Xu, Weiting; Chen, J.J.; Wei, Jiangxiong; Zhang, Bin; Yuan, Xiongzhou; Xu, Peng; Yu, Qijun; Ren, Jie
Highlights: WFT is the governing parameter for the rheological performance of ZP mortar. Permeable porosity is the controlling parameter of the hardened performance of ZP mortar. Addition of 5% ZP yields the highest flowability and the cohesiveness of mortar. Use of 5–10% ZP as the cement substitute in mortar is proposed. Abstract: Due to the pozzolanicity and grindability, zeolite had undeniable advantages to be used as a supplementary cementitious material for reduction of cement consumption and carbon footprint of concrete production. Since the study on the effects of zeolite powder (ZP) addition on rheological and hardened properties of cementitious mortar system was rare in literature, the purpose of this study was undertaken to reveal this subject. A total of 25 mortar mixes with various ZP contents at various water/binder (W/B) ratios were prepared and subjected to flowability, cohesiveness, adhesiveness compressive strength and permeable porosity tests. In-depth analysis revealed that the water film thickness (WFT) combined the effect of solid packing density, water demand and solid surface area, and hence governed the rheological property of the cementitious composite; the permeable porosity was proved to be the key governing parameter for the hardened performance of cementitious mortar. Addition of ZP exerted its influence on the performance of mortar via changing the WFT and permeable porosity of the cementitious composite system. For achieving a sound balance between the rheological and mechanical property of cementitious composite, a lower permeable porosity at the same WFT or a higher WFT at the same permeable porosity was pursued. The regression analysis results of concurrent permeable porosity-WFT quantified the positive effect of the partial substitution of Portland cement by 5–10% of ZP was affordable in all aspects.